RELEASE OF ARSENIC ASSOCIATED WITH THE REDUCTION AND TRANSFORMATION OF IRON OXIDES - Pedersen H.D.; Postma D.; Jakobsen R. (My University, 2006)
The behaviour of trace amounts of arsenate coprecipitated with ferrihydrite, lepidocrocite and goethite was studied during reductive dissolution and phase transformation of the iron oxides using [55Fe]- and [73As]-labelled iron oxides. The As/Fe molar ratio ranged from 0 to 0.005 for ferrihydrite and lepidocrocite and from 0 to 0.001 for goethite. For ferrihydrite and lepidocrocite, all the arsenate remained associated with the surface, whereas for goethite only 30% of the arsenate was desorbable. The rate of reductive dissolution in 10 mM ascorbic acid was unaffected by the presence of arsenate for any of the iron oxides and the arsenate was not reduced to arsenite by ascorbic acid. During reductive dissolution of the iron oxides, arsenate was released incongruently with Fe2+ for all the iron oxides. For ferrihydrite and goethite, the arsenate remained adsorbed to the surface and was not released until the surface area became too small to adsorb all the arsenate. In contrast, arsenate preferentially desorbs from the surface of lepidocrocite. During Fe2+ catalysed transformation of ferrihydrite and lepidocrocite, arsenate became bound more strongly to the product phases. X-ray diffractograms showed that ferrihydrite was transformed into lepidocrocite, goethite and magnetite whereas lepidocrocite either remained untransformed or was transformed into magnetite. The rate of recrystallization of ferrihydrite was not affected by the presence of arsenate. The results presented here imply that during reductive dissolution of iron oxides in natural sediments there will be no simple correlation between the release of arsenate and Fe2+. Recrystallization of the more reactive iron oxides into more crystalline phases, induced by the appearance of Fe2+ in anoxic aquifers, may be an important trapping mechanism for arsenic.
Keywords: ARSENIC; DISSOLUTION; IRON OXIDE; PHASE TRANSITION; REDUCTION; TRACE ELEMENT